2002
DOI: 10.1063/1.1496124
|View full text |Cite
|
Sign up to set email alerts
|

Structural and magnetic transformation of monodispersed iron oxide particles in a reducing atmosphere

Abstract: Uniform metal iron ellipsoidal particles of around 200 nm in length were obtained by reduction and passivation of alumina-coated ␣ -Fe 2 O 3 ͑hematite͒ particles under different conditions of temperature and hydrogen flow rate. The monodispersed hematite particles were prepared by the controlled hydrolysis of ferric sulfate and further coated with a homogeneous thin layer of Al 2 O 3 by careful selection of the experimental conditions, mainly pH and aluminum salt concentration. The reduction mechanism of ␣ -Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 21 publications
1
36
0
1
Order By: Relevance
“…Studies on the reduction in magnetization in iron oxide nanoparticles (γ-Fe 2 O 3 , Fe 3 O 4 ) had reported that reduction is because of the existence of noncollinear spins at the surface of the nanoparticles 5,23 . Varanda et al 24 described a linear correlation between Ms and nanoparticles size suggesting that defects at the nanoparticle surface can influence the magnetic properties 5,24 . The surface curvature of particles was higher for nanoparticles which stimulated disordered crystal orientation on the surface resulting in significantly decreased Ms…”
Section: Resultsmentioning
confidence: 99%
“…Studies on the reduction in magnetization in iron oxide nanoparticles (γ-Fe 2 O 3 , Fe 3 O 4 ) had reported that reduction is because of the existence of noncollinear spins at the surface of the nanoparticles 5,23 . Varanda et al 24 described a linear correlation between Ms and nanoparticles size suggesting that defects at the nanoparticle surface can influence the magnetic properties 5,24 . The surface curvature of particles was higher for nanoparticles which stimulated disordered crystal orientation on the surface resulting in significantly decreased Ms…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the produced nanoparticles have less value of M s than that of the particles with large volume. Authors of [28] found a linear relationship between parameter M s and sizes of the nanoparticles; they explained it by the highly developed surface. According to the studies of the specific surface, there is a clusters layer of ~ 2 nm in size on each nanoparticle, which partially prevents dipole-dipole interaction between particles, despite their strong agglomeration.…”
Section: Methodsmentioning
confidence: 99%
“…Also, in magnetite fine particles, Varanda et al have reported a linear correlation between saturation magnetization and particle size, suggesting that defects at the particle surface can influence the magnetic properties. The surface curvature of the NP was much larger for smaller particle size, which encouraged disordered crystal orientation on the surface and thus resulted in significantly decreased Ms in smaller NPs (Varanda et al, 2002b). In this context, advancement in the use of magnetic particles for biomedical applications depends on the new synthetic methods with better control of the size distribution, magnetic properties and the particle surface characteristics.…”
Section: Synthesis Of Magnetic Nanoparticlesmentioning
confidence: 99%